2012
DOI: 10.1136/gutjnl-2012-302717
|View full text |Cite
|
Sign up to set email alerts
|

Serological markers predict inflammatory bowel disease years before the diagnosis

Abstract: A panel of serological markers is able to predict development of CD and UC in individuals from a low-risk population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 34 publications
(28 reference statements)
4
82
0
Order By: Relevance
“…Although none of them is currently recommended instead of or in addition to ASCA determination, a combination of pANCA, ASCA, anti-CBir1 and anti-OmpC were shown to predict CD and UC in individuals from a low-risk population several years before any clinical sign of the disease [80]. Moreover, it has been suggested that anti-GP2 IgG and IgA serum autoantibodies combined with ASCA are of potential clinical utility in distinguishing CD from UC [36,81], but that they may also be helpful in distinguishing between ileocolonic and colonic CD [35].…”
Section: Serum Markers To Define Type Of Ibdsmentioning
confidence: 99%
“…Although none of them is currently recommended instead of or in addition to ASCA determination, a combination of pANCA, ASCA, anti-CBir1 and anti-OmpC were shown to predict CD and UC in individuals from a low-risk population several years before any clinical sign of the disease [80]. Moreover, it has been suggested that anti-GP2 IgG and IgA serum autoantibodies combined with ASCA are of potential clinical utility in distinguishing CD from UC [36,81], but that they may also be helpful in distinguishing between ileocolonic and colonic CD [35].…”
Section: Serum Markers To Define Type Of Ibdsmentioning
confidence: 99%
“…[37][38][39][40] These biomarkers predict and are qualitatively and quantitatively associated with an aggressive and complicated course of Crohn's disease, including stricturing and/or penetrating phenotype, both in adult and paediatric patients. 13 However, a recent study showed that none of the anti-glycan antibodies ASCA, AMCA, ACCA, ALCA, anti-L and anti-C correlates with disease phenotype.…”
Section: Antimicrobial Antibodiesmentioning
confidence: 99%
“…In light of these considerations, it would seem advantageous to have multiplex tests (microarray, blot) using predefined profiles [7], in which diverse markers are tested simultaneously with the objective of providing a complete report, useful either for diagnostic orientation (Crohn's disease, ulcerative colitis or celiac disease) or for determining risk stratification. Multiple pathology-oriented antibody profiles might, in addition, demonstrate their usefulness in predicting IBD onset in the pre-diagnostic phase, as already demonstrated for ASCA [8], and very recently for anti-CBir1 and anti-OmpC [9] that have been detectable in the sera of apparently healthy subjects, on average 3-4 years before the disease became manifest, thus introducing a window of opportunity for early intervention.…”
mentioning
confidence: 99%